The Influence of Light Intensity and Leaf Movement on Photosynthesis Characteristics and Carbon Balance of Soybean - Feng, Lingyang; Raza, Muhammad Ali; Li, Zhongchuan; Chen, Yuankai; Khalid, Muhammad Hayder Bin; Du, Junbo; Liu, Weiguo; Wu, Xiaoling; Song, Chun; Yu, Liang; Zhang, Zhongwei; Yuan, Shu; et al. (Frontiers in Plant Science, 2019)
In intercropping systems shading conditions significantly impair the seed yield and quality of soybean, and rarely someone investigated the minimum amount of light requirement for soybean growth and development. Therefore, it is an urgent need to determine the threshold light intensity to ensure sustainable soybean production under these systems. An integrated approach combining morphology, physiology, biochemistry and genetic analysis was undertaken to study the light intensity effects on soybean growth and development. A pot experiment was set up in a growth chamber under increasing light intensity treatments of 100 (L100), 200 (L200), 300 (L300), 400 (L400) and 500 (L500) μmol m-2 s-1. Compared with L100, plant height, hypocotyl length and abaxial leaf petiole angle were decreased, biomass, root:shoot ratio and stem diameter were increased, extremum was almost observed in L400 and L500. Leaf petiole movement and leaf hyponasty in each treatment has presented a tendency to decrease the leaf angle from L500 to L100. In addition, the cytochrome content (Chl a, Chl b, Car), net photosynthetic rate, chlorophyll fluorescence values of Fv/Fm, Fv'/Fm', ETR, ΦPSII and qP were increased as the light intensity increased, and higher values were noted under L400. Leaf microstructure and chloroplast ultrastructure positively improved with increasing light intensity, and leaf-thickness, palisade, and spongy tissues-thickness were increased by 105%, 90%, and 370%, under L500 than L100. Moreover, the cross-sectional area of chloroplast (C) outer membrane and starch grains (S), and sectional area ratio (S:C) was highest under L400 and L500, respectively. Compared to L100, the content of starch granules increased by 35.5%, 122.0%, 157.6%, and 145.5%, respectively in L400. The same trends were observed in the enzyme activity of sucrose-synthase, sucrose phosphate synthase, starch synthase, rubisco, phosphoenol pyruvate carboxykinase and phosphoenol pyruvate phosphatase. Furthermore, sucrose synthesis-related genes were also up-regulated by increasing light intensity, and the highest seed yield and yield related parameters were recorded in the L400. Overall, these results suggested that 400 and 500 μmol m-2 s-1 is the optimum light intensity which positively changed the leaf orientation and adjusts leaf angle to perpendicular to coming light, consequently, soybean plants grow well under prevailing conditions.